Research Data Services in European Academic Research Libraries - Tenopir, Carol; Talja, Sanna; Horstmann, Wolfram; Late, Elina; Hughes, Dane; Pollock, Danielle; Schmidt, Birgit; Baird, Lynn; Sandusky, Robert; Allard, Suzie (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2017)
Research data is an essential part of the scholarly record, and management of research data is increasingly seen as an important role for academic libraries. This article presents the results of a survey of directors of the Association of European Research Libraries (LIBER) academic member libraries to discover what types of research data services (RDS) are being offered by European academic research libraries and what services are planned for the future. Overall, the survey found that library directors strongly agree on the importance of RDS. As was found in earlier studies of academic libraries in North America, more European libraries are currently offering or are planning to offer consultative or reference RDS than technical or hands-on RDS. The majority of libraries provide support for training in skills related to RDS for their staff members. Almost all libraries collaborate with other organizations inside their institutions or with outside institutions in order to offer or develop policy related to RDS. We discuss the implications of the current state of RDS in European academic research libraries, and offer directions for future research.